A Mixture of Functionally Oligoclonal Humanized Monoclonal Antibodies That Neutralize Clostridium difficile TcdA and TcdB with High Levels ofIn VitroPotency ShowsIn VivoProtection in a Hamster Infection Model - Nicola L. Davies; Joanne Compson; Brendon MacKenzie; Victoria O’Dowd; Amanda Oxbrow; James T. Heads; Alison Turner; Kaushik Sarkar; Sarah Dugdale; Mark Jairaj; Louis Christodoulou; David Knight; et al. (2013)
Clostridium difficile infections are a major cause of antibiotic-associated diarrhea in hospital and care facility patients. In spite of the availability of effective antibiotic treatments, C. difficile infection (CDI) is still a major cause of patient suffering, death, and substantial health care costs. Clostridium difficile exerts its major pathological effects through the actions of two protein exotoxins, TcdA and TcdB, which bind to and disrupt gut tissue. Antibiotics target the infecting bacteria but not the exotoxins. Administering neutralizing antibodies against TcdA and TcdB to patients receiving antibiotic treatment might modulate the effects of the exotoxins directly. We have developed a mixture of three humanized IgG1 monoclonal antibodies (MAbs) which neutralize TcdA and TcdB to address three clinical needs: reduction of the severity and duration of diarrhea, reduction of death rates, and reduction of the rate of recurrence. The UCB MAb mixture showed higher potency in a variety of in vitro binding and neutralization assays (∼10-fold improvements), higher levels of protection in a hamster model of CDI (82% versus 18% at 28 days), and higher valencies of toxin binding (12 versus 2 for TcdA and 3 versus 2 for TcdB) than other agents in clinical development. Comparisons of the MAb properties also offered some insight into the potential relative importance of TcdA and TcdB in the disease process.